Harnessing flour recovery in the Indian wheat - MOHAN, D; GUPTA, R K; SHARMA, INDU (The Indian Journal of Agricultural Sciences, 2026)
Flour recovery in 100 wheat (Triticum aestivum L.) varieties samples received from different locations and regions of India during 2005-11was studied for its association with baking and 15 other grain quality parameters. Differences in flour recovery were noticed between and within different regions of the country. Environmental influence in flour yield was not consequential due to absence of crop year variations and the varietal interactions with crop years and locations were also insignificant. In certain regions, interaction between locations and crop years assumed significance and sites with better flour recovery could be noticed. Wheat from peninsular region was rated best for milling yield, i e 71% whereas the most productive wheat land of the country, i e north western plains, was restricted to 68% only. Wheat grown in northern hills was very poor with flour yield as low as 65%. Suitable varieties and most conducive locations were suggested to harness flour recovery in different parts. Relationship between extraction rate and end-product quality was very strong and positive with bread volume, bread and chapati qualities; and negative with biscuit spread factor. Impact of various physico-chemical grain properties was affirmative, except for Ã¢ carotene. Route to flour yield was examined through multiple regression analysis and the key contributing traits were test weight, grain appearance, grain protein content, sedimentation value, grain hardness index and certain micronutrients like iron, copper and manganese. Backward multiple regression analysis emphasised high contribution of some micronutrients like copper and iron, under various trait combinations. Contribution of these constituents varied at the regional level, strategy for genetic improvement in flour yield, therefore, would also vary accordingly. Defining constituent grain parameters in Indian varieties shall be useful to develop varieties with enhanced flour recovery.